2009
DOI: 10.1177/0961203308094360
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic thrombocytopenic purpura in systemic lupus erythematosus: risk factors and clinical outcome: a single centre study

Abstract: The study was undertaken to investigate clinical characteristics of thrombotic thrombocytopenic purpura (TTP) in patients with SLE and to determine risk factors and clinical outcome of TTP in patients with SLE. Among the 1203 patients with SLE admitted to catholic medical centre of the catholic university of Korea from January 1990 to December 2006, 26 patients with SLE were found to admit with TTP. TTP was defined if microangiopathic haemolytic anaemia, thrombocytopenia and negative Coombs' test were present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
2
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 29 publications
5
65
2
5
Order By: Relevance
“…low platelet count and increased LDH) [4]. He also had a history of lupus nephritis, which is an independent risk factor for TTP development [5]. The patient's ADAMTS-13 levels were also severely reduced while the ADAMTS-13 IgG antibody assay was positive.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…low platelet count and increased LDH) [4]. He also had a history of lupus nephritis, which is an independent risk factor for TTP development [5]. The patient's ADAMTS-13 levels were also severely reduced while the ADAMTS-13 IgG antibody assay was positive.…”
Section: Discussionmentioning
confidence: 96%
“…SLEDAI scores tended to improve as platelet counts and LDH levels normalized. Another retrospective study showed that independent risk factors for acquired TTP include a high SLEDAI score (C10) and co-existing nephritis [5]. A study comparing idiopathic TTP (iTTP) with SLE-associated TTP (sTTP) also observed that all sTTP patients had active SLE at TTP diagnosis and more renal involvement than iTTP [6].…”
Section: Introductionmentioning
confidence: 97%
“…TTP can present in approximately 2% of the patients with SLE [8]. In most cases, it appears in patients previously diagnosed and treated for SLE for several years, with a high SLE disease activity index score and renal involvement [7].…”
Section: Discussionmentioning
confidence: 99%
“…TTP, an uncommon life threatening disease, can present in approximately 2 % of the patients with SLE. Very rarely TTP presents simultaneously with SLE [1].Moreover waiting for complete evolution of pentad features significantly delays treatment and worsens the outcome [2]. The treatment options include plasma exchange using fresh frozen plasma (FFP)/cryosupernatant (CSP) and immunosuppressive therapy [3].…”
Section: Introductionmentioning
confidence: 99%